Breakfast at Tiffany's - Edwards, Blake, 1922-; Jurow, Martin; Shepherd, Richard A., 1927-; Axelrod, George; Hepburn, Audrey, 1929-1993.; Peppard, George; Neal, Patricia, 1926-; Ebsen, Buddy, 1908-2003.; Balsam, Martin, 1919-1996.; Rooney, Mickey; Mancini, George; Capote, Truman, 1924-1984.; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2006)
A romantic comedy about an eccentric New York City playgirl determined to marry a Brazillian millionaire and her next-door neighbor, a writer who is sponsored--and stifled--by a wealthy woman.
Title from container.
Based on the novel by Truman Capote.
Originally released as a motion picture in 1961.
Special features: Commentary by producer Richard Shepherd; the making of a classic; it's so Audrey: a style icon; brilliance in a blue box; Audrey's letter to Tiffany; original theatrical trailer.
Audrey Hepburn, George Peppard, Patricia Neal, Buddy Ebsen, Martin Balsam, Mickey Rooney.
DVD, region 1, widescreen (aspect ratio 16:9); Dolby Digital.
Keywords: Man-woman relationships; Young women -- Conduct of life; Authors; American fiction -- 20th century; Manhattan (New York, N.Y.) -- Social life and customs; Feature films; Romantic comedy films; Films for the hearing impaired; Feature films; Comedy films; Comedy; Romance